Dumbbell Defect Containing Chromium-Rich Lithium-Vacant Layered LiyCr1-xFexO2 (y ≤ 1, 0 ≤ x ≤ 0.2): An Unexplored and Highly Efficient Electrocatalyst for the Oxygen Evolution Reaction - Soni V.; Mondal R.; Singh A.N.; Singh P.; Gupta A. (My University, 2025)
Oxygen electrochemistry plays a critical role in water electrolysis, fuel cells, and metal-air batteries as efficient energy storage and conversion technology to harness renewable energies. Dumbbell defects containing chromium-rich lithium-vacant layered structure LiCrO2 are envisaged here as an efficient oxygen evolution reaction (OER) electrocatalyst due to the presence of Cr6+ ions at interstitial sites that facilitates −Cr-O-OH formation in basic media. The presence of Cr6+ ions at the dumbbell interstitial sites of the hexagonal close-packed LiCrO2 lattice was confirmed by X-ray photoelectron spectroscopy and Fourier transform infrared spectroscopy studies. The crystal structure, morphology, and composition of the materials were confirmed by powder X-ray diffraction, scanning electron microscopy, high-resolution transmission electron microscopy, and inductively coupled plasma-mass spectrometry analysis. Rhombohedral structure formation and formation of Cr6+ ion interstitials in the Li layer increase that varies with Fe doping in LiyCr1-xFexO2 (y ≤ 1, 0 ≤ x ≤ 0.2), and the best OER activity is achieved for Li0.6Cr0.9Fe0.1O2 (LCFO-10) with a Tafel slope of 50 mV dec-1 and an overpotential of 311 mV at a current density of 10 mA cm-2, better than that of the RuO2 (overpotential ∼336 mV) benchmark catalyst. At an overpotential of 350 mV, the OER current density of LCFO-10 is 28.07 mA cm-2, which is ∼2 times higher than the OER current density observed with commercial RuO2 (13.22 mA cm-2), indicating its superior electrocatalytic performances. The remarkable enhancement of OER performance may be attributed to the synergistic interaction of Cr6+ and Fe3+ ions present in the lattice. © 2023 American Chemical Society.